2018
DOI: 10.1186/s12966-018-0737-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of childhood overweight and obesity and its association with weight-related attitudes and behaviors in China: a national longitudinal study

Abstract: BackgroundChildhood obesity is a major public health challenge. We aimed to investigate the incidence of overweight/obesity among Chinese children; and prospectively examine the associations of weight-change intention with risk of overweight/obesity and behavioral changes in initially normal-weight children.MethodsA national sample of 21,796 children aged 6–17 years were investigated in September 2013 and followed up nine months later, of which 19,887 (91%) were normal weight and 1909 (9%) were underweight at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In China’s education system, it relies almost entirely on test scores to evaluates progress, which lead to more reading, examinations, or/and homework for Chinese children and less time for physical activities [8]. In 2013, approximately 23.0% and 14.0% of Chinese boys and girls aged 2–19 years were overweight or obese [9]. Overweightness and obesity in children and adolescents can lead to developmental problems, such as poor cognitive function and altered timing of puberty [8].…”
Section: Introductionmentioning
confidence: 99%
“…In China’s education system, it relies almost entirely on test scores to evaluates progress, which lead to more reading, examinations, or/and homework for Chinese children and less time for physical activities [8]. In 2013, approximately 23.0% and 14.0% of Chinese boys and girls aged 2–19 years were overweight or obese [9]. Overweightness and obesity in children and adolescents can lead to developmental problems, such as poor cognitive function and altered timing of puberty [8].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic analysis reported that the rates of overweight/obesity in developing and developed countries were 13% and 24%, respectively, in 2013 4 . The Nutrition and Chronic Diseases of Chinese Residents Report in 2015 showed that the prevalence of overweight and obesity in children < 6 years of age was 8.4% and 3.1%, respectively, and these rates are increasing 2,6 . Childhood overweight and obesity are closely related to the occurrence of chronic diseases such as hypertension, diabetes and coronary heart disease 3,5 and also have a negative association with mental health, intellectual and learning abilities, personality development and psychosocial well‐being 1…”
Section: Introductionmentioning
confidence: 99%
“…4 The Nutrition and Chronic Diseases of Chinese Residents Report in 2015 showed that the prevalence of overweight and obesity in children < 6 years of age was 8.4% and 3.1%, respectively, and these rates are increasing. 2,6 Childhood overweight and obesity are closely related to the occurrence of chronic diseases such as hypertension, diabetes and coronary heart disease 3,5 and also have a negative association with mental health, intellectual and learning abilities, personality development and psychosocial well-being. 1 Recent increases in the rates of childhood obesity and associated health risks have drawn the attention of scientists.…”
Section: O R I G I N a L R E S E A R C H I N F A N T S A N D C H I L D R E N Introductionmentioning
confidence: 99%
“…A systematic analysis reported that the rates of overweight/obesity in developing and developed countries were 13% and 24%, respectively, in 2013 [4]. The Nutrition and Chronic Diseases of Chinese Residents Report (2015) showed that the prevalence of overweight and obesity in children < 6 years of age was 8.4% and 3.1%, respectively, and these rates are increasing [2,6]. Childhood overweight and obesity are closely related to the occurrence of chronic diseases such as hypertension, diabetes, and coronary heart disease [3,5] and also have a negative association with mental health, intellectual and learning abilities, personality development, and psychosocial well-being [1].…”
Section: Introductionmentioning
confidence: 99%